Innovative Strategies in Tendon Tissue Engineering - Eleonora Bianchi; Marco Ruggeri; Silvia Rossi; Barbara Vigani; Dalila Miele; Maria Cristina Bonferoni; Giuseppina Sandri; Franca Ferrari (MDPI AG, 2021)
The tendon is a highly aligned connective tissue that transmits force from muscle to bone. Each year, more than 32 million tendon injuries have been reported, in fact, tendinopathies represent at least 50% of all sports injuries, and their incidence rates have increased in recent decades due to the aging population. Current clinical grafts used in tendon treatment are subject to several restrictions and there is a significant demand for alternative engineered tissue. For this reason, innovative strategies need to be explored. Tendon replacement and regeneration are complex since scaffolds need to guarantee an adequate hierarchical structured morphology and mechanical properties to stand the load. Moreover, to guide cell proliferation and growth, scaffolds should provide a fibrous network that mimics the collagen arrangement of the extracellular matrix in the tendons. This review focuses on tendon repair and regeneration. Particular attention has been devoted to the innovative approaches in tissue engineering. Advanced manufacturing techniques, such as electrospinning, soft lithography, and three-dimensional (3D) printing, have been described. Furthermore, biological augmentation has been considered, as an emerging strategy with great therapeutic potential.